2012
DOI: 10.1055/s-0032-1315129
|View full text |Cite
|
Sign up to set email alerts
|

Percent Mammographic Density and Dense Area as Risk Factors for Breast Cancer

Abstract: !Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Our clearer finding of a mammographic risk association with early-onset breast cancer than that typically studied could also be relevant to western women, for whom there is relatively little information. The positive associations between mammographic density measures and the risk of breast cancer found in the present study are consistent with findings from previous studies of women from western populations who were typically older than those in our study (Maskarinec and Meng, 2000;Ursin et al, 2003;Maskarinec et al, 2005;Kerlikowske et al, 2010;Heusinger et al, 2011;Rauh et al, 2012;Razzaghi et al, 2012). When we categorized the study population into percent density groups to allow comparison with previous studies, we found that Korean women in the highest mammographic percent density group (>50%) had a 2.98-fold increased risk of breast cancer compared with those in the lowest mammographic percent density group (< 5%) after adjusting for covariates.…”
Section: Discussionsupporting
confidence: 93%
“…Our clearer finding of a mammographic risk association with early-onset breast cancer than that typically studied could also be relevant to western women, for whom there is relatively little information. The positive associations between mammographic density measures and the risk of breast cancer found in the present study are consistent with findings from previous studies of women from western populations who were typically older than those in our study (Maskarinec and Meng, 2000;Ursin et al, 2003;Maskarinec et al, 2005;Kerlikowske et al, 2010;Heusinger et al, 2011;Rauh et al, 2012;Razzaghi et al, 2012). When we categorized the study population into percent density groups to allow comparison with previous studies, we found that Korean women in the highest mammographic percent density group (>50%) had a 2.98-fold increased risk of breast cancer compared with those in the lowest mammographic percent density group (< 5%) after adjusting for covariates.…”
Section: Discussionsupporting
confidence: 93%
“…Cases and controls were collected from 2002 to 2008 [26][27][28][29]. The BBCC is part of the Breast Cancer Association Consortium (BCAC) and has taken part in the validation of confirmed breast cancer susceptibility single nucleotide polymorphisms (SNPs) [30][31][32][33][34][35][36][37][38].…”
Section: Patient Cohortmentioning
confidence: 99%
“…A four- to six-fold greater risk of breast cancer has been reported in women having more than 75% of the total area on mammogram occupied by dense area 13. In addition to PDA, absolute dense area of the breast obtained on assessment of PDA has been reported to be an independent risk factor for breast cancer, and its inclusion in risk-assessment tools has been proposed 14. Female survivors of Hodgkin’s disease that were treated with chest irradiation are known to be at an increased risk of breast cancer, with the cumulative absolute risks of breast cancer varying with type of therapy, age at end of follow-up, time since diagnosis, and radiation dose 15.…”
Section: Introductionmentioning
confidence: 99%